(untitled) (Research, Society and Development, 2022)
The beauty standard currently imposed by society, aiming at the perfect body, has been one of the primary factors for the increase in cases of eating disorders such as bulimia and anorexia nervosa, bringing with it several harms to the body, including damage to oral health, characterized by increased carious lesions, decreased saliva (xerostomia), perimolysis, among others, being caused mainly by poor oral hygiene, vitamin deficiency and saliva acidification resulting from frequent vomiting. The dental surgeon is often the first professional to come into contact with such alterations, and is able to identify the disease and offer due help to the patient, being able to carry out the appropriate dental treatment for the case, always counting on the help of a multidisciplinary team to treat it.